ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERCEIVED VALUE DALAM MEMBENTUK LOYALITAS PADA PELANGGAN E-COMMERCE BUKALAPAK DI KOTA SEMARANG - Satria, Dinda; Khasanah, Imroatul (Diponegoro Journal of Management, 2021)
This purpose of this study is to analyze the effect of promotion, website quality, and service quality on loyalty to E-commerce customers with perceived value as an intervening variable. The population used in this study is Bukalapak users in Semarang City. The number of samples used in this study were 120 respondents. The data collection method used is through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques with the AMOS version 21.0 program.The results showed that promotion, website quality, and service quality had a positive and significant effect on perceived value. Other results also show that perceived value has a positive and significant effect on customer loyalty.